Effects of gut microbiota in breast cancer - Kang, Leping; Chen, Haiyang; He, Chengjun; Li, Junchuan (Frontiers in Oncology, 2025)
Breast cancer (BC) stands as the predominant form of cancer affecting women globally, with its etiology rooted in a complex interplay of factors. Emerging research underscores the significant impact of microbiota on the development of BC. Evidence points to a correlation between BC and microbial imbalance, not only within the intestinal milieu but also in breast tissue itself. Alterations in the diversity and functionality of bacterial populations in these areas are implicated in the disease’s pathogenesis.The intestinal microbiota exerts a pivotal influence on the metabolism of steroid hormones, including estrogens, which are recognized as critical elements in the risk profile for BC, particularly among women who have reached menopause. These hormones can drive the onset and advancement of BC via multiple mechanisms. Concurrently, a body of research highlights the contributory roles of immune system elements, inflammatory processes, dietary patterns, and the use of probiotics in the context of BC. Understanding this intricate interplay holds promise for developing innovative therapeutic approaches